A STRUCTURAL ANALYSIS OF INTRODUCTION AND PROLOGUE IN BRITISH FAIRY TALES - M. Payziboyeva (American Journals, 2024)
The article examines the structure of the introduction and prologue found in British fairy tales and explores their characteristics. Traditional beginnings used in British fairy tales are analyzed and examples are given.
Keywords: Folktale, prologue, introduction, fairy tale, beginning, plot, mono-plot, multi-plot, hero, magic.